2015
DOI: 10.1007/s12088-015-0537-5
|View full text |Cite
|
Sign up to set email alerts
|

Strain Improvement of Streptomyces xanthochromogenes RIA 1098 for Enhanced Pravastatin Production at High Compactin Concentrations

Abstract: Pravastatin is one of the most popular cholesterol-lowering drugs. Its industrial production represents a two-stage process including the microbial production of compactin and its further biocatalytic conversion to pravastatin. To increase a conversion rate, a higher compactin content in fermentation medium should be used; however, high compactin concentrations inhibit microbial growth. Therefore, the improvement of the compactin resistance of a producer still remains a relevant problem. A multi-step random UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…After optimizing the fermentation medium, the maximum bioconversion rate of this strain reached 91% at a daily compactin dose of 1 g L −1 , and remained high (83%) even at a doubled dose of 2 g L −1 (Figure 3G). [ 82 ]…”
Section: Genetic Strategies Improving Statins Productionmentioning
confidence: 99%
“…After optimizing the fermentation medium, the maximum bioconversion rate of this strain reached 91% at a daily compactin dose of 1 g L −1 , and remained high (83%) even at a doubled dose of 2 g L −1 (Figure 3G). [ 82 ]…”
Section: Genetic Strategies Improving Statins Productionmentioning
confidence: 99%
“… Immobilization on silane modified iron (II, III) oxide magnetic nanoparticles (MNP) Cholesterol → 4-cholesten-3-one Oxidation → cholesterol oxidase Immobilized cholesterol oxidase activity was 2 times higher than its free form; it could be reused for up to 10 cycles Not reported Ghosh et al 2018 Streptomyces sp. Immobilization on silicon dioxide-coated magnetite biosensor Cholesterol → 4-cholesten-3-one Oxidation → cholesterol oxidase Immobilized enzyme was more than 2 times efficient than its free form; enzyme concentration was 20 mg·mL -1 , substrate concentration was 6.46 mM; it could be reused for up to 30 days 90.0% in 180 min Perdani et al 2020 Streptomyces strain(s) Mutated, genetically modified, or heterologous expressed enzymes bioconversion Substrate(s) → product(s) Reaction → enzyme(s) Bioconversion conditions Bioconversion rate/yield/productivity References Streptomyces xanthochromogenes RIA 1098 Multi-step random UV mutagenesis Compactin → pravastatin - Mutagenesis was performed in order to obtain mutants resistant for high compactin concentrations; 50 h of reaction time 91.0 % Dzhavakhiya et al 2015 Streptomyces coelicolor CR1 Structure-guided engineering and directed evolution Ethyl-4-chloro-3-oxobutyrate → ethyl-(S)-4-chloro-3-hydroxylbutyrate Reduction → carbonyl reductase Mutagenesis was performed to improve both thermal stability and catalytic activity; substrate concentration = 100 g·L -1 ; bioreactor = 300 mL; reaction time = 9 h 255 g· L −1 day -1 Li et al 2017 Streptomyces halstedii Heterologous expression in Pichia pastoris and displaying on its membrane surface Phosphatidylcholine + l -serine → phosphatidylserine Transphosphatidylation → phospholipase D Repeated batch conditions up to 4 cycles: 8 h reaction; 200 mL of 0.2 M sodium acetate buffer; 40 °C, pH 5,5; 3 U·mL -1 biocatalyst; 1:3 phosphatidylcholine: l -serine ratio 53.0% Liu et al 2019 Streptomyces sp. NRRL F-4489 Heterologous expression in E. coli BL21 (DE3) ...…”
Section: Biotechnological Biotransformation Processes For Drug Producmentioning
confidence: 99%
“…For example, multi-step random UV mutagenesis has been recently applied to Streptomyces xanthochromogenes strain RIA 1098 for the production of pravastatin, one of the most popular cholesterol-lowering drugs (Dzhavakhiya et al 2015 ). The traditional industrial two-stage process includes the microbial synthesis of compactin by Penicillium citrinum and then its further conversion to pravastatin by S. xanthochromogenes strain RIA 1098, which is capable of hydroxylating the compactin on the C6 position (Dzhavakhiya et al 2015 ). A high compactin content is required to increase the rate of conversion, but at the same time high compactin concentrations could inhibit microbial growth.…”
Section: Biotechnological Biotransformation Processes For Drug Producmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins are mainly derived from secondary metabolites of microbial fermentation and chemical synthesis. One study of various microorganisms revealed some fungi and bacteria that can convert compactin to pravastatin, in addition to strain improvement of Streptomyces xanthochromogenes RIA 1098 for enhanced pravastatin production ( 7 ). Pravastatin is mainly used to reduce cholesterol levels in patients, and it has been confirmed to promote angiogenesis and resistance to oxidative stress ( 8 , 9 ), but its role in intestinal I/R injury has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%